Countering Others' Insurgencies Understanding U.S. Small-Footprint Interventions in Local Context - Watts, Stephen (RAND Corporation, 2014)
This report describes counterinsurgency strategies and practices and conditions in which U.S. "small-footprint" partnerships may succeed. Successful U.S. operations have been concentrated in favorable conditions, but most insurgencies occur in worst-case conditions. Case studies of the Philippines and Pakistan reinforce findings of the analysis and highlight challenges for the U.S. in trying to influence partners. Recommendations are offered for managing troubled partnerships.